COMPONENTS OF THE OBJECT OF PUBLIC MANAGEMENT OF TERRITORIAL DEVELOPMENT - Kraskivska, N.V. (Global Prosperity, 2025)
Abstract. The article provides a comprehensive analysis of the process of forming the components of the object of state management of territorial development of Ukraine. It is shown that in the conditions of deep socio-economic transformations, decentralization of power, European integration processes and military challenges, the issue of effective territorial development is gaining strategic importance for Ukraine. Territorial development today is not only a spatial organization of the economy, but a complex process that encompasses the economic, social, infrastructural, environmental and institutional dimensions of the functioning of regions and communities. Mechanisms of state management of territorial development are a key tool for ensuring balanced development of regions, reducing inter-territorial disparities, increasing the competitiveness of territories and the quality of life of the population. They must be adaptive to different types of territories, able to take into account their resource potential, demographic characteristics and level of economic activity. It has been established that the concepts and theories of sustainable territorial development form the necessary foundation for substantiating strategic priorities, mechanisms and instruments for achieving balanced and inclusive development of countries, regions and communities, taking into account economic, social and environmental imperatives. They are based on the key principles of sustainable development - integration of economic, social and environmental dimensions, orientation on the needs of current and future generations, ensuring justice and inclusiveness, taking into account the limitations of natural capital, adaptation to the local context. The implementation of these principles requires comprehensive and coordinated efforts of all levels of public administration and stakeholders with the active participation of the public. It has been proven that the economic, social and environmental components form the triune basis of sustainable territorial development. Achieving sustainability requires a comprehensive and integrated approach to these dimensions, taking into account their interrelationships, synergies and compromises for public administration entities. This involves the transformation of traditional models of socio-economic development and environmental management on the principles of efficiency, inclusiveness, balance and sustainability. The key drivers of such transformation are innovation, stakeholder cooperation, good governance, responsible production and consumption. The integration of social, economic and environmental dimensions of sustainable development is reflected in the goals and objectives of state management of territorial development in Ukraine.